Stimulus-specific and adaptive value representations in the basolateral amygdala in male mice - Julian Hinz; Mathias Mahn; Sigrid Müller; András Szőnyi; Tobias Eichlisberger; Andreas Lüthi (Nature Communications)
Abstract Animals make decisions based on the value of potential outcomes. This perceived value is not fixed; it changes depending on internal needs, such as hunger or thirst, and past experiences. The basolateral amygdala (BLA) is known to be crucial for updating predicted reward values. However, it has been unclear how the BLA represents the specific value of different rewards. Two-photon calcium imaging in male mice showed that population response magnitude scaled with subjective value, and different rewards recruited distinct neuronal subpopulations. Value representations quickly re-scaled when a novel, higher-value reward appeared, and internal state shaped them: thirst selectively boosted responses to water, whereas aversive experience dampened sucrose responses. Thus, BLA circuits carry flexible, stimulus-specific value signals that integrate relative value and current affective or homeostatic conditions, providing a neural basis for adaptive decision making and learning. Our findings reveal that the BLA maintains adaptable, reward-specific value signals, essential for guiding choices according to current needs and changing circumstances.